How breast cancer treatments affect the quality of life of women with non-metastatic breast cancer one year after surgical treatment: a cross-sectional study in Greece - Yfantis, Aris; Sarafis, Pavlos; Moisoglou, Ioannis; Tolia, Maria; Intas, George; Tiniakou, Ioanna; Zografos, Konstantinos; Zografos, George Constantine; Constantinou, Marianna; Nikolentzos, Athanasios; Kontos, Michalis (My University, 2020)
Background: The continuously increasing survivorship of female breast cancer makes the monitoring and improvement of patients' quality of life ever so important. While globally there is a growing body of research on health-related quality of life 1 year after surgical treatment for non-metastatic breast cancer, up-to-date information regarding Greek patients is scarce. Objective: To measure the level of QoL of non-metastatic BC survivors in Greece 1 year after surgery. Methods: A sample of 200 female breast cancer survivors aged 18 to 75, who followed up as outpatients in five public hospitals were included in this cross-sectional study. All recruited patients agreed to participate in the study (100% response rate). Quality of life data were collected through the EORTC QLQ-C30 as well as BR23 questionnaires. Results: Cronbach's alpha for all scales of the two questionnaires was from 0.551 to 0.936 indicating very good reliability. According to the Multiple Linear Regression, older patients showed a lower future perspective (p =.031), with those living in rural areas, which was associated with more financial difficulties (p =.001). Women with tertiary education and those who had been hospitalized in a university hospital recorded better on global health status (p =.003 and.000 respectively). Patients who underwent chemotherapy reported better scores in the emotional function sub-scale (p =.025). Women with reconstruction and at least one complication appeared to have significantly better scores in future perspective and social function (p =.005,.002 respectively). Conclusions: Breast cancer survivors were found to have an overall good quality of life, functioning/symptoms scores and were satisfied with the provided care.
Keywords: Adjuvant therapy; Breast cancer; Care; Quality of life; Surgery